Polysaccharide Composites with Rosa canina for Sustained Anti-Inflammatory Skin Therapy - Anghel, Narcis; Apostol, Irina; Plaesu, Ioana; Mija, Alice; Simionescu, Natalia; Coroaba, Adina; Spiridon, Iuliana (Polymers, 2025)
This study presents novel skin-compatible biomaterials based on guar gum and dextran sulfate matrices, incorporating softwood lignin, lignin esterified with aspartic acid, and Rosa canina extract. The materials were prepared via casting and evaluated for physicochemical, mechanical, and biological properties. Spectroscopic analyses confirmed successful lignin esterification, with new carbonyl and amide peaks and a nitrogen signal (3.83%) detected. Rosa canina extract enhanced the Young’s modulus from 1.42 MPa to 3.18 MPa and reduced elongation at break from 34.88 mm to 25.19 mm. The combination of esterified lignin and Rosa canina showed the greatest mechanical reinforcement (3.74 MPa modulus, 23.78 mm elongation). Swelling capacity decreased from 0.40 to 0.23 g water/g material and followed pseudo-second-order kinetics (R2 = 0.991–0.998). The release of Rosa canina bioactives followed the Makoid–Banakar model, indicating a transition from rapid to sustained release. All formulations exhibited anti-inflammatory activity with over 45% protein denaturation inhibition, peaking at 61.58% for the Rosa canina-only sample. In vitro biocompatibility assays demonstrated over 80% cell viability, confirming the potential of these biomaterials for dermal applications.